2018
DOI: 10.13080/z-a.2018.105.029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a growth regulator Ribav-Extra on winter wheat seedlings exposed to heavy metals

Abstract: We studied the influence of a natural plant growth regulator Ribav-Extra and ions of heavy metals (HM) Pb 2+ , Cu 2+ , Zn 2+ and Ni 2+ on the physiological and biochemical indices of the winter wheat (Triticum aestivum L. ) cultivar 'Mironovskaya 808'. The seeds of wheat were treated with Ribav-Extra (10 ppm) and grown for 7 days on heavy metal salt solutions (10 μM or 1 mM). After that we recorded heavy metals accumulation, growth, generation of superoxide anion ( • O 2 − ), lipid peroxidation (LPO), and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…In this study, we document the first ever use of commercial Epin-Extra ® (with an 24-EpiB base) and RE as alternative PGRs. Previously, these natural PGRs were used only for seed treatment, spraying plants, or processing cuttings, and these treatments resulted in an enhanced tolerance to abiotic stresses (Lukatkin and Pogodina, 2012;Lukatkin et al, 2013a;2013b;Bashmakov et al, 2016;Gruznova et al, 2018). We also showed that these PGRs may be used as alternative PGRs in the in vitro culture of carnation (Dianthus caryophyllus L.) (Lukatkin et al, 2017).…”
Section: Pgrs Play a Major Role In Cymbidium Organogenesismentioning
confidence: 59%
See 2 more Smart Citations
“…In this study, we document the first ever use of commercial Epin-Extra ® (with an 24-EpiB base) and RE as alternative PGRs. Previously, these natural PGRs were used only for seed treatment, spraying plants, or processing cuttings, and these treatments resulted in an enhanced tolerance to abiotic stresses (Lukatkin and Pogodina, 2012;Lukatkin et al, 2013a;2013b;Bashmakov et al, 2016;Gruznova et al, 2018). We also showed that these PGRs may be used as alternative PGRs in the in vitro culture of carnation (Dianthus caryophyllus L.) (Lukatkin et al, 2017).…”
Section: Pgrs Play a Major Role In Cymbidium Organogenesismentioning
confidence: 59%
“…A presowing treatment of wheat seeds with RE (10 ppm or 10 !3 %) decreased the negative impact of heavy metals (Cu, Zn, Ni, or Pb) by reducing oxidative stress by suppressing O 2•G generation, lipid peroxidation intensity, and catalase activity. This suggests that wheat plants whose seeds had been treated with RE were more heavy metal-resistant than untreated plants (Gruznova et al, 2018). The treatment of maize seeds with RE changed parameters related to oxidative stress (the generation of superoxide anion and the intensity of lipid peroxidation) and stimulated increased antioxidative activity in maize seedlings under unfavorable temperatures.…”
Section: Pgrs Play a Major Role In Cymbidium Organogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…An endogenous phenolic PGR such as salicylic acid (SA) governs an imperative role in plant physiological processes (photosynthesis, growth, and development), specifically under abiotic stresses, including Cd toxicity ( Tran and Popova, 2013 ; Gruznova et al, 2018 ). Ahmad et al (2011) highlighted that SA in initial growth stages assisted plants in mitigating increased damage caused by Cd toxicity by expressing specific proteins and defense-related enzymes ( Çanakci and Dursun, 2012 ; Roychoudhury et al, 2016 ).…”
Section: Remediation Of Cadmium-polluted Soilsmentioning
confidence: 99%
“…The advantage of using plant growth regulators is their ability to increase the efficiency of plant nutrient utilization and maximize the fulfillment of genetic and physiological potentials (Jung et al, 2018), being non-toxic to plants and the environment and neutralizing the effects of heavy metals in soil (Gruznova, 2018). Growth regulators are responsible for important processes in the plant, boosting the resistance to abiotic stresses and stimulating the growth and development (Upreti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%